Pendampingan Kader dalam Pelayanan Kesehatan Interprofesional dapat Meningkatkan Derajat Kesehatan Lansia di Desa Penuktukan Buleleng 2024 - Ribek, Nyoman Ribek (STIKES Advaita Medika Tabanan, 2025)
Abstract The main strategy of health development is to empower the community to live a healthy lifestyle and increase access to quality health services. The problem is that the implementation system is still fragmented, and holistic and integrated health services . Therefore, efforts are needed to improve health services in collaboration between health professionals . Penuktukkan village in Buleleng has a population of 3,803 people with the age of 60-74 as much as 73.6%, 52.8% rarely move 71.7% do not participate in posyandu and 52.8% rarely get health services. The goal of Community Service is to reduce the problem of non-communicable diseases. The activity method is to provide health education and interprofessional services, mentoring and coaching elderly cadres. The result of the service is an increase in knowledge, from an average score of 60 to 91 with a difference in Sig value (2- tailed) which means there is a significant difference. Interprofessional services included nutrition counseling, laboratory examination, breast cancer examination and biomassage treatment. The community of 45 people with the results of a decrease in blood pressure from 132 mmHg to 120 mmHg, average cholesterol 173 mg/dl, sugar 140 mg/dl and uric acid 7.2 mg/dl. As a result, Elderly cadres can provide education and services to the elderly independently and health workers from the puskesmas are more enthusiastic in empowering cadres and the community. It is concluded that elderly cadres are more understanding in improving Elderly Health services. It is recommended that elderly cadres be further improved in interprofessional services. Keywords: Intervention, Interprofessional, Elderly Cadre